A new approach to evaluate the impact of thermophysical properties of nanofluids on heat transfer and pressure drop - Abdelrazek, Ali H.; Alawi, Omer A.; Kazi, Salim Newaz; Yusoff, Nukman; Chowdhury, Zaira Zaman; Sarhan, Ahmed Aly Diaa Mohammed (Elsevier, 2018)
In this paper, an experimental and numerical study was conducted to evaluate the impacts of momentum and thermal diffusivity comparing to the thermal conductivity of various types of nanofluids on turbulent forced convection heat transfer. 1%, 2%, and 3% volumetric concentrations of different nanofluids such as Al2O3-DW, SiO2-DW, and Cu-DW were considered in this study and their properties were evaluated numerically at the flow inlet temperature of 30 °C. The experimental works were conducted with distilled water as a working fluid to validate the 2-D numerical model. A two-dimensional domain was constructed using ANSYS-Fluent package, and the standard k–ε turbulence model was employed to solve the continuity, momentum, and energy equations. The flow was maintained in the Reynolds range between 6000 and 12,000, and the data obtained experimentally were validated by results from empirical correlations. The numerical solutions for the average Nusselt number and pressure drop presents a good agreement with the experimental results as the average error was less than 5% for both the cases of heat transfer and pressure loss data. The results showed that Al2O3-DW nanofluid has the best enhancement in convection heat transfer coefficient compared with the DW and other nanofluids of the same concentration while Cu-DW nanofluids shown the lowest enhancement though it shown the highest value of thermal conductivity. Also, the results showed that the product of kinematic and dynamic viscosities had the greatest effect on pressure drop in the fluid domain.